Dating among female college students - Delasa, Mary Joy C.
The main objective of this study is to describe the female college students' idea of date and dating. Specifically, the study aims to understand college students' ideas of dating; To describe the common characteristics of individuals dated by college students; To know the common characteristics that their parents would like; To determine what are the common perceived consequences if they have go against their parents idea of a good dat and to identify the common perceived rewards if they follow their parents idea of a good date. The researcher used fishbowl sampling in deriving the names of the respondents of the study. The data were collected using the interview schedule and analyzed using simple frequency counts and percentages., This study shows that female college students consider dating as going out with the guy alone with dinner as it's most popular and usual activity. The study describes the common characteristics of the guy that they have dated; These are guys with sense of humor, are respectful, fun to be with, clean and intelligent. There are two factors affecting the idea of a suitable date and these are the educational background of the guy and the religious affiliation of the guy. Study shows that parents' idea of a suitable date are guys who have good educational background; guys who are college graduates or have the same educational level as their daughters. The common perceived reward whenever respondents follow their parents' wishes is for the guy to be welcome when he visits the girl in her house. The study also shows that respondents are aware that their parents will be strict on them when they will not follow their parents' wishes.